Kazakhstan : Strategic Review of the Mining and Metallurgy Sector - World Bank (Washington, DC, 2013)
Kazakhstan is exceptionally endowed with petroleum, and mineral resources. However, since independence, the vast majority of new investment in the sector has been devoted to petroleum, while, new investment in the mining, and metallurgical sector has not been commensurate with the country's geological potential, or with the importance of a sector accounting for over thirty percent of total export earnings, ten percent of GDP, and nineteen percent of total industrial employment. The study focuses on the minerals legislation, and regulation as the corner stone of development of the mining, and metallurgy sector, governing access by the private sector to mineral rights, highlighting the country's fundamental problem, i.e., the confusion of the mining and metallurgy, with the oil/gas sector, pointing that the economics of the two sectors are entirely different. It outlines the tendering system for blocks of geologically prospective ground contemplated in the legislation, while a practice extensively used in oil/gas industry, is quite uncommon in mining/metallurgy, actually proven an unsuccessful practice. Moreover, mining taxation as applied to mining and metallurgy is fundamentally unattractive to new investment, and not competitive internationally. In order to fairly administer the legislation, public institutions are essential, where the focus should be on funding, logistical support, and training of professionals, thus far insufficient for long term sustainability. It is recommended that government proceed with a responsible program of divestiture, such as the reactivation of the "blue chips" program, and include environmental, and infrastructure considerations.